Did the COVID-19 pandemic change the pattern of trauma and its outcomes? Experiences of the National Trauma Registry of Iran - Hamid Reza Jahantigh; Mohammadreza Zafarghandi; Vafa Rahimi-Movaghar; Vali Baigi; Esmaeil Fakharian; Hamid Pahlavanhosseini; Habibollah Pirnejad; Reza Farahmand Rad; Salman Daliri; Mehdi Nasr Isfahani; Moein Khormali; Seyed Mohammad Piri; et al. (Archives of Trauma Research)
Background: This study aimed to compare the characteristics of traumatic injuries before and during the COVID-19 pandemic.Methods: In this study, data of trauma patients admitted to the six hospitals affiliated with the National Trauma Registry of Iran (NTRI) before (from April 21, 2017, to February 19, 2020) and during (from February 20, 2020, to November 30, 2021) the COVID-19 pandemic were used. The data were collected by interviewing and patients’ documents, including demographic data, cause of injury, in-hospital mortality, and diagnostic and therapeutic procedures.Results: Seventeen thousand four traumatic patients were included in the registry. The mean of monthly admitted patients declined from 360 patients before the COVID-19 pandemic to 213 patients during the pandemic. The percentage of conflict/interpersonal violence and self-harm/suicide among all registered traumas increased from 2.9% and 0.8% before the COVID-19 pandemic to 5.3% and 2.4 during the COVID-19 pandemic, respectively (Ps<0.001). Additionally, the percentage of registered patients with fall injuries before the COVID-19 pandemic was 27.5% and reached 24.6% during the COVID-19 pandemic. Moreover, before the pandemic, ICU admissions and in-hospital mortality were 9.8% and 1.1%, respectively, and reached 12.7% and 1.8% during the pandemic (Ps <0.001). Furthermore, the HLOS decreased from 148.5 (SD=570.7) hours to 117.4 (SD=226.6) hours (p<0.001).Conclusion: The findings reveal that the COVID-19 pandemic led to several significant changes in the patterns of trauma patients admitted to the NTRI centers, including gender, age, and cause of trauma and it increased the ICU admissions and in-hospital mortalities and reduced HLOS.